Sick at work: presenteeism among nurses in a Portuguese public hospital - Martinez, L. F.; Ferreira, A. I. (Stress and Health, 2012)
Presenteeism refers to attending work despite being ill. This article focuses on this innovative organizational concept. Data from nurses at a major Portuguese public hospital (N?=?296) reported some major causes of presenteeism, namely lower-back pain, breath infections, migraines and stress. Although females revealed higher prevalence levels for most of the presenteeism causes, no gender differences were found regarding the number of hours people were affected by presenteeism. Moreover, other work variables were correlatedage, perceived health state, number of working hours, income and senioritywith a presenteeism scale (SPS-6) and a Health Condition Index. Most importantly, a negative correlation was found between perceived health status and presenteeism. Additionally, more experienced and highly paid nurses tended to be less affected by presenteeism. Finally, the limitations of this studyas well as some implications of presenteeism on productivity lossare discussed.